Pole piece and preparation method thereof, battery cell, battery and electric equipment

By designing and laying active structures with different particle sizes in the electrode sheet to form through holes, the problem of high tortuosity of thick electrodes is solved, better infiltration of the electrolyte and longitudinal diffusion of ions are achieved, and the dynamic performance of the battery is optimized.

CN119833535AActive Publication Date: 2025-04-15CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311435893.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-04-15
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The thick electrode structure has a high tortuosity, resulting in the extension of the lithium ion transmission path, increasing the battery impedance, and endangering the dynamic performance.

Method used

A pole sheet is designed, and its active layer is laminated to form through holes, regulate the pore size, reduce tortuosity, and increase the infiltration of the electrolyte and ion longitudinal diffusion channels.

Benefits of technology

By adjusting the pore size structure of the electrode sheet, the tortuosity of the thick electrode is reduced, the infiltration and ion diffusion capabilities of the electrolyte are improved, and the dynamic performance of the battery is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833535A_ABST
    Figure CN119833535A_ABST
Patent Text Reader

Abstract

The invention discloses a pole piece and a preparation method thereof, a battery cell, a battery and electric equipment. The pole piece comprises a foil, a first active layer and a second active layer, the first active layer is stacked on the foil and comprises a first active structure and a second active structure which are connected with each other; the second active layer is stacked on the first active layer, the second active layer comprises a third active structure and a fourth active structure which are connected, the third active structure is stacked on the first active structure, and the fourth active structure is stacked on the second active structure; the particle size D50 of the main material of the first active structure is smaller than the particle size D50 of the main material of the second active structure; or the particle size D50 of the main material of the fourth active structure is smaller than the particle size D50 of the main material of the third active structure. According to the pole piece, the tortuosity of the thick electrode is reduced, the infiltration of electrolyte and the longitudinal diffusion channel of ions are increased, and the dynamic performance of the battery is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a pole piece and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art

[0002] The energy density and power density of power batteries are mutually restrictive and both are crucial. The surface density of the electrode is continuously improved in order to obtain higher energy density.

[0003] Improving the compaction of electrodes is a common method to increase the volumetric energy density of batteries. The pore structure of the electrode is important for the infiltration of the electrolyte and the liquid phase transport of lithium ions. However, thick electrodes often lead to longer lithium ion transport paths with high tortuosity, which increases the impedance of the battery and harms the battery's kinetic performance. Summary of the invention

[0004] The purpose of the present invention is to provide a pole piece and a preparation method thereof, a battery cell, a battery and an electrical device to solve the problem of high tortuosity of thick electrode structures.

[0005] To achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a pole piece, comprising:

[0007] Foil; a first active layer, stacked on the foil, the first active layer comprising a first active structure and a second active structure connected to each other; a second active layer, stacked on the first active layer, the second active layer comprising a third active structure and a fourth active structure connected to each other, the third active structure stacked on the first active structure, and the fourth active structure stacked on the second active structure; the particle size D of the main material of the first active structure 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

[0008] In one embodiment, the particle size D of the main material of the first active structure is 50 Smaller than the particle size D of the main material of the second active structure 50 ; and the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

[0009] In one embodiment, the first active structure comprises a first main material, and the particle size D of the first main material is 50D1 satisfies: 0.3 μm ≤ D1 ≤ 0.6 μm, the second active structure has a second main material, and the particle size D 50 is D2, satisfying: 0.9 μm ≤ D2 ≤ 1.3 μm; the third active structure has a third main material, and the particle size D of the third main material is 50 is D3, satisfying: 0.9 μm ≤ D3 ≤ 1.3 μm, the fourth active structure has a fourth main material, the particle size D of the fourth main material 50 It is D4, satisfying: 0.3μm≤D4≤0.6μm.

[0010] In one embodiment, the first active structure has a first conductive agent, and the specific surface area of ​​the first conductive agent is A1, which satisfies: 80m 2 / g≤A1≤110m 2 / g, the second active structure has a second conductive agent, the specific surface area of ​​the second conductive agent is A2, and satisfies: 80m 2 / g≤A2≤110m 2 / g; the third active structure has a third conductive agent, the specific surface area of ​​the third conductive agent is A3, satisfying: 30m 2 / g≤A3≤60m 2 / g, the fourth active structure has a fourth conductive agent, the specific surface area of ​​the fourth conductive agent is A4, and satisfies: 30m 2 / g≤A4≤60m 2 / g.

[0011] In one embodiment, the first active structure also has a first binder, and the mass ratio of the first main material, the first binder and the first conductive agent is 100: (2.0-2.5): (0.6-1.2); the second active structure also has a second binder, and the mass ratio of the second main material, the second binder and the second conductive agent is 100: (2.0-2.5): (0.6-1.2); the third active structure also has a third binder, and the mass ratio of the third main material, the third binder and the third conductive agent is 100: (2.0-2.5): (0.2-0.6); the fourth active structure also has a fourth binder, and the mass ratio of the fourth main material, the fourth binder and the fourth conductive agent is 100: (2.0-2.5): (0.2-0.6).

[0012] In one embodiment, the oil absorption values ​​of the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent are B, which satisfies: 240 ml / 100 g ≤ B ≤ 320 ml / 100 g.

[0013] In one embodiment, the first active layer includes a plurality of the first active structures and a plurality of the second active structures, and the plurality of the first active structures and the plurality of the second active structures are alternately arranged; the second active layer includes a plurality of the third active structures and a plurality of the fourth active structures, and the plurality of the third active structures and the plurality of the fourth active structures are alternately arranged.

[0014] In a second aspect, the present invention provides a method for preparing a pole piece, comprising the following steps:

[0015] Provide foil;

[0016] Laying a first active structure and a third active structure on the foil, and laminating a second active structure and a fourth active structure on the foil on the same side of the first active structure and the third active structure;

[0017] The first active structure and the second active structure are connected to form a first active layer, the third active structure and the fourth active structure are connected to form a second active layer, and the particle size D of the main material of the first active structure is 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

[0018] In one embodiment, a first active structure and a third active structure are stacked on the foil, and a second active structure and a fourth active structure are stacked on the same side of the first active structure and the third active structure, including:

[0019] Providing a first coating die and a second coating die;

[0020] Providing a slurry, wherein the slurry includes a first slurry, a second slurry, a third slurry, and a fourth slurry;

[0021] The first coating die coats the first slurry and the third slurry on the foil to form the first active structure and the third active structure, and the second coating die coats the second slurry and the fourth slurry on the foil to form the second active structure and the fourth active structure.

[0022] In a third aspect, the present invention provides a battery cell, comprising a diaphragm and the pole piece described in the first aspect, wherein the diaphragm and the pole piece are stacked.

[0023] In a fourth aspect, the present invention provides a battery, comprising a housing and the battery cell described in the third aspect, wherein the battery cell is accommodated in the housing.

[0024] In a fifth aspect, the present invention provides an electrical equipment, comprising an electrical device and the battery described in the fourth aspect, wherein the battery supplies power to the electrical device.

[0025] The pole piece provided by the present invention is provided with a stacked first active layer and a second active layer, and the particle size D of the main material of the first active structure in the first active layer is 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure in the second active layer 50 Smaller than the particle size D of the main material of the third active structure 50 That is, the active material layer is arranged into areas with different particle sizes, so that straight through holes are directly formed at the interface of large and small particles during the rolling process, thereby realizing the regulation of the pore size in the longitudinal vertical direction, reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of ions, and optimizing the battery kinetic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a cross-sectional view of a pole piece of an embodiment;

[0028] Figure 2 is a flow chart of a method for preparing a pole piece according to an embodiment;

[0029] Figure 3 The present invention is a flow chart of one of the steps in a method for preparing a pole piece according to an embodiment.

[0030] Description of reference numerals:

[0031] 10 - first active layer, 11 - first active structure, 12 - second active structure, 20 - second active layer, 21 - third active structure, 22 - fourth active structure. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0034] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0035] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0036] refer to Figure 1 The present invention provides a pole piece, including a foil, a first active layer 10 and a second active layer 20.

[0037] The first active layer 10 is stacked on the foil, and the first active layer 10 includes a first active structure 11 and a second active structure 12 connected to each other. The second active layer 20 is stacked on the first active layer 10, and the second active layer 20 includes a third active structure 21 and a fourth active structure 22 connected to each other, the third active structure 21 is stacked on the first active structure 11, and the fourth active structure 22 is stacked on the second active structure 12; the particle size D of the main material of the first active structure 11 is 50 Smaller than the particle size D of the main material of the second active structure 12 50 ; or the particle size D of the main material of the fourth active structure 22 50 Smaller than the particle size D of the main material of the third active structure 21 50 .

[0038] When the electrode is a positive electrode, the foil material may include but is not limited to any one of aluminum foil, composite aluminum foil or carbon-coated aluminum foil; when the electrode is a negative electrode, the foil material may include but is not limited to any one of copper foil, composite copper foil or carbon-coated copper foil.

[0039] The electrode sheet is provided with a stacked first active layer 10 and a second active layer 20, and the particle size D of the main material of the first active structure 11 in the first active layer 10 is 50 Smaller than the particle size D of the main material of the second active structure 12 50 ; or the particle size D of the main material of the fourth active structure 22 in the second active layer 20 50 Smaller than the particle size D of the main material of the third active structure 21 50, that is, the active material layer is arranged into regions with different particle sizes, so that the interface between large and small particles directly forms through holes during the rolling process, realizing the regulation of the pore size in the vertical direction, reducing the tortuosity of the thick electrode, increasing the electrolyte infiltration and the longitudinal diffusion channel of ions, without causing more energy consumption, and optimizing the battery dynamics performance. Among them, the particle size D of the main material 50 It refers to the average particle size of the active material in the first active layer 10 and the second active layer 20. The particle size D of the main material 50 It can be directly obtained by testing the powder material with a particle size analyzer; it can also be obtained by measuring the particle size of the main material in the corresponding area of ​​the SEM image, and using statistical methods to obtain the average particle size.

[0040] In one embodiment, the particle size D of the main material of the first active structure 11 is 50 Smaller than the particle size D of the main material of the second active structure 12 50 ; and the particle size D of the main material of the fourth active structure 22 50 Smaller than the particle size D of the main material of the third active structure 21 50 , so that in the double-layer structure, the interface of large and small particles directly forms straight through holes during the rolling process, realizing the regulation of the pore size in the longitudinal vertical direction, further reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of ions, without causing more energy consumption, and optimizing the battery kinetic performance.

[0041] In one embodiment, the lengths of the first active structure 11 and the third active structure 21 in the first direction are equal; and / or the lengths of the second active structure 12 and the fourth active structure 22 in the first direction X are equal. The first direction X is a direction perpendicular to the coating direction and parallel to the surface of the foil. Such a structural design is conducive to further extending the through holes formed in each layer of the double-layer structure based on the interface of large and small particles during the rolling process, thereby reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of the ions, and will not bring more energy consumption, thereby optimizing the battery dynamics performance.

[0042] In one embodiment, the first active structure 11 comprises a first main material, and the particle size D of the first main material is 50 D1 satisfies: 0.3 μm ≤ D1 ≤ 0.6 μm, the second active structure 12 has a second main material, and the particle size D of the second main material 50 is D2, satisfying: 0.9 μm ≤ D2 ≤ 1.3 μm; the third active structure 21 has a third main material, and the particle size D of the third main material is 50 D3 satisfies: 0.9 μm ≤ D3 ≤ 1.3 μm, the fourth active structure 22 has a fourth main material, and the particle size D of the fourth main material is 50 It is D4, satisfying: 0.3μm≤D4≤0.6μm.

[0043] Particle size D of the first main material 50 D1 can be 0.3μm, 0.4μm, 0.5μm, 0.6μm, etc. without limitation.

[0044] Particle size D of the second main material 50 D2 can be 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, etc. without limitation.

[0045] Particle size D of the third main material 50 D3 can be 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, etc. without limitation.

[0046] The particle size D of the fourth main material 50 D4 can be 0.3μm, 0.4μm, 0.5μm, 0.6μm, etc. without limitation.

[0047] The particle size of the main material is regulated so that when the electrode is rolled, micron-sized straight pores can be directly formed at the interface between large and small particles. This will not affect the solid-phase conduction of lithium ions in the main material itself, but can increase the liquid-phase transmission of lithium ions and electrolyte infiltration without causing more energy consumption.

[0048] In one implementation, the first main material and the fourth main material are the same, and the second main material and the third main material are the same, which can ensure the surface density and compaction consistency of the pole piece.

[0049] In one embodiment, the first active structure 11 has a first conductive agent, and the specific surface area of ​​the first conductive agent is A1, which satisfies: 80m 2 / g≤A1≤110m 2 / g, the second active structure 12 has a second conductive agent, the specific surface area of ​​the second conductive agent is A2, and satisfies: 80m 2 / g≤A2≤110m 2 / g; the third active structure 21 has a third conductive agent, the specific surface area of ​​the third conductive agent is A3, satisfying: 30m 2 / g≤A3≤60m 2 / g, the fourth active structure 22 has a fourth conductive agent, the specific surface area of ​​the fourth conductive agent is A4, and satisfies: 30m 2 / g≤A4≤60m 2 / g.

[0050] A1 can be 85m 2 / g≤A1≤105m 2 / g, 90m 2 / g≤A1≤100m 2 / g, etc., specifically 80m 2 / g, 85m 2 / g, 90m 2 / g、100m 2 / g、105m 2 / g, 110m 2 / g, etc., without restriction.

[0051] A2 can be 85m 2 / g≤A2≤105m 2 / g, 90m 2 / g≤A2≤100m 2 / g, etc., specifically 80m 2 / g, 85m 2 / g, 90m 2 / g、100m 2 / g、105m 2 / g, 110m 2 / g, etc., without restriction.

[0052] A3 can be 35m 2 / g≤A3≤55m 2 / g, 40m 2 / g≤A3≤50m 2 / g, etc., specifically 30m 2 / g, 35m 2 / g, 40m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, etc., without restriction.

[0053] A4 can be 35m 2 / g≤A4≤55m 2 / g, 40m 2 / g≤A4≤50m 2 / g, etc., specifically 30m 2 / g, 35m 2 / g, 40m 2 / g, 50m 2 / g, 55m 2 / g, 60m 2 / g, etc., without restriction.

[0054] The upper layer uses conductive agents with low specific surface areas (i.e., the third conductive agent and the fourth conductive agent) to reduce the barrier to the diffusion of lithium ions in the liquid phase, and the lower layer uses conductive agents with high specific surface areas (i.e., the first conductive agent and the second conductive agent) to increase electron transfer between particles.

[0055] In one embodiment, the first active structure 11 also has a first binder, and the mass ratio of the first main material, the first binder and the first conductive agent is 100: (2.0-2.5): (0.6-1.2); the second active structure 12 also has a second binder, and the mass ratio of the second main material, the second binder and the second conductive agent is 100: (2.0-2.5): (0.6-1.2); the third active structure 21 also has a third binder, and the mass ratio of the third main material, the third binder and the third conductive agent is 100: (2.0-2.5): (0.2-0.6); the fourth active structure 22 also has a fourth binder, and the mass ratio of the fourth main material, the fourth binder and the fourth conductive agent is 100: (2.0-2.5): (0.2-0.6).

[0056] The mass ratio of the first main material, the first adhesive and the first conductive agent can be 100:2.0:0.6, 100:2.2:1.0, 100:2.5:1.2, etc., without limitation.

[0057] The mass ratio of the second main material, the second adhesive and the second conductive agent can be 100:2.0:0.6, 100:2.2:1.0, 100:2.5:1.2, etc., without limitation.

[0058] The mass ratio of the third main material, the third adhesive and the third conductive agent can be 100:2.0:0.2, 100:2.2:0.4, 100:2.5:0.6, etc., without limitation.

[0059] The mass ratio of the fourth main material, the fourth adhesive and the fourth conductive agent can be 100:2.0:0.2, 100:2.2:0.4, 100:2.5:0.6, etc., without limitation.

[0060] The mass ratio of the third conductive agent and the fourth conductive agent to the first conductive agent and the second conductive agent may be 1:2.5.

[0061] The types of binders include one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, without limitation.

[0062] The first active structure 11 and the second active structure 12 on the side close to the foil have a higher content of conductive agent, which helps to enhance the current collector's ability to collect current. The third active structure 21 and the fourth active structure 22 on the side close to the separator have a low content of conductive agent, which helps to reduce tortuosity and promote the transmission of lithium ions. Designing the content of conductive agent according to the gradient of conductive demand is not only conducive to improving dynamic performance, but also can reduce the amount of conductive agent used, further improving energy density.

[0063] In one embodiment, the oil absorption value of the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent is B, which satisfies: 240 ml / 100 g≤B≤320 ml / 100 g.

[0064] B may be 250ml / 100g≤B≤310ml / 100g, 260ml / 100g≤B≤300ml / 100g, 270ml / 100g≤B≤290ml / 100g, etc., specifically 240ml / 100g, 250ml / 100g, 260ml / 100g, 270ml / 100g, 290ml / 100g, 300ml / 100g, 310ml / 100g, 320ml / 100g, etc. without limitation.

[0065] The specific surface area of ​​the conductive agent is tested according to the national standard GB / T 19587; the oil absorption value of the conductive agent is tested according to the national standard GB / T 19587 using a specific surface area tester.

[0066] Conductive agents with high oil absorption values ​​can increase the liquid saturation capacity of the electrode, which is similar to providing a miniature lithium storage pool. Conductive agents with high oil absorption values ​​form a local microscopic lithium ion concentration field between particles, promoting the liquid phase transmission of lithium ions under the concentration gradient.

[0067] In one embodiment, the first active layer 10 includes a plurality of first active structures 11 and a plurality of second active structures 12, and the plurality of first active structures 11 and the plurality of second active structures 12 are alternately arranged, and the second active layer includes a plurality of third active structures 21 and a plurality of fourth active structures 22, and the plurality of third active structures 21 and the plurality of fourth active structures 22 are alternately arranged.

[0068] Multiple active structures are arranged alternately, and micron-scale pore channels are formed at the interface of large and small particles during rolling, which helps to reduce the tortuosity of the electrode, increase the infiltration of the electrolyte and the longitudinal diffusion channel of ions, and optimize the battery kinetic performance.

[0069] refer to Figure 2 and Figure 3 The present invention provides a method for preparing a pole piece, comprising the following steps:

[0070] Step S10, providing a foil;

[0071] Step S20, stacking the first active structure 11 and the third active structure 21 on the foil, and stacking the second active structure 12 and the fourth active structure 22 on the foil on the same side of the first active structure 11 and the third active structure 21;

[0072] The first active structure 11 and the second active structure 12 are connected to form the first active layer 10, and the third active structure 21 and the fourth active structure 22 are connected to form the second active layer 20. The particle size D of the main material of the first active structure 11 is 50 Smaller than the particle size D of the main material of the second active structure 12 50 ; or the particle size D of the main material of the fourth active structure 22 50 Smaller than the particle size D of the main material of the third active structure 21 50 .

[0073] The particle size D of the main material of two adjacent active structures on the same active material layer 50 Different, different active material layers are stacked and the particle size D of the main material of two adjacent active structures 50 different.

[0074] The electrode sheet is provided with a stacked first active layer 10 and a second active layer 20. The particle size D of the main material of the first active structure 11 is 50 Smaller than the particle size D of the main material of the second active structure 12 50 ; or the particle size D of the main material of the fourth active structure 22 50 Smaller than the particle size D of the main material of the third active structure 21 50 That is, the active material layer is arranged into areas with different particle sizes, so that straight through holes are directly formed at the interface of large and small particles during the rolling process, thereby realizing the regulation of the pore size in the longitudinal vertical direction, reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of ions, and optimizing the battery kinetic performance.

[0075] In one implementation, step S20 includes step S21, step S22, and step S23, including:

[0076] Step S21, providing a first coating die and a second coating die;

[0077] Step S22, providing slurry, the slurry includes a first slurry, a second slurry, a third slurry and a fourth slurry;

[0078] In step S23 , the first coating die coats the first slurry and the third slurry on the foil to form the first active structure 11 and the third active structure 21 , and the second coating die coats the second slurry and the fourth slurry on the foil to form the second active structure 12 and the fourth active structure 22 .

[0079] The first slurry includes a first main material, a first conductive agent, and a first adhesive; the second slurry includes a second main material, a second conductive agent, and a second adhesive; the third slurry includes a third main material, a third conductive agent, and a third adhesive; the fourth slurry includes a fourth main material, a fourth conductive agent, and a fourth adhesive.

[0080] When the electrode sheet is a positive electrode sheet, the main material is a positive electrode material, which can be a phosphate positive electrode active material and a ternary positive electrode active material. In a specific embodiment, it includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, fluorolithium vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. This application does not specifically limit these materials, and appropriate materials can be selected according to actual application requirements.

[0081] When the electrode sheet is a negative electrode sheet, the main material is the negative electrode material, which can be a carbon-based negative electrode material or a non-carbon-based negative electrode material. The carbon-based negative electrode material includes at least one of a graphite material and a non-graphite material; wherein the graphite material includes at least one of natural graphite or artificial graphite; the non-graphite material includes at least one of a hard carbon material or a soft carbon material; the non-carbon-based negative electrode material can be a titanium-based material, a tin-based material, a silicon-based material, a nitride, etc.

[0082] The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 (carbon 60) and carbon nanotubes; the types of binders have been described in the above embodiments. This application does not specifically limit these materials, and appropriate materials can be selected according to actual application requirements.

[0083] In one embodiment, a plurality of first coating dies and a plurality of second coating dies are alternately arranged.

[0084] The first coating die head generates the first active structure 11 and the third active structure 21, and the second coating die head generates the second active structure 12 and the third active structure 21. After baking and rolling, straight through holes are formed at the interface of large and small particles, thereby realizing the regulation of the pore size in the longitudinal vertical direction, reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of the ions, and optimizing the battery kinetic performance.

[0085] The present invention provides a battery core, comprising a diaphragm and a pole piece according to any one of the aforementioned embodiments, wherein the diaphragm and the pole piece are stacked.

[0086] The separator can be any one of woven membrane, non-woven membrane (non-woven fabric), microporous membrane, composite membrane, rolled membrane, etc., without limitation. The separator is in contact with the third active structure 21 and the fourth active structure 22. The third active structure 21 and the fourth active structure 22 have a smaller specific surface area of ​​the conductive agent and a lower content of the conductive agent, which helps to reduce the liquid phase mass transfer resistance and promote the transmission of lithium ions.

[0087] The present invention provides a battery, comprising a shell and a battery core according to any one of the above embodiments, wherein the battery core is accommodated in the shell.

[0088] The battery may be a square shell battery, a cylindrical battery, or other types such as a prismatic battery, without limitation.

[0089] The shell is a material with high structural strength, specifically metal materials, high-strength plastics, ceramics, etc. Metal materials such as aluminum, aluminum alloys, magnesium alloys, iron and iron alloys, etc. The shell includes a bottom plate and side plates. The shell can be an integrated structure, that is, the bottom plate and the side plates are an integrated structure made by an integrated molding process. The integrated molding process can be specifically stamping, casting, etc., without limitation. The shell can also be a split structure, and the side plate and the bottom plate can be connected and fixed by welding, bonding, clamping, screwing, etc. The wall thickness of the shell can be roughly uniform everywhere, that is, the thickness of the side plate can be roughly uniform, and the thickness of the bottom plate and the side plate can also be roughly the same.

[0090] The particle size D of the main material of the first active structure 11 and the fourth active structure 22 on the electrode of the battery is 50 Smaller than the particle size D of the main material of the second active structure 12 and the third active structure 21 50 , so that straight through holes are directly formed at the interface of large and small particles during the rolling process, the pore size in the longitudinal vertical direction is regulated, the tortuosity of the thick electrode is reduced, the infiltration of the electrolyte and the longitudinal diffusion channel of the ions are increased, no more energy consumption is caused, and the battery kinetic performance is optimized.

[0091] The present invention also provides an electrical device, comprising an electrical device and a battery as described in any of the above embodiments, wherein the battery supplies power to the electrical device. The electrical device may be a television, a washing machine, a car, etc., without limitation.

[0092] The technical solution of the present application is described in detail below through specific embodiments.

[0093] Example 1

[0094] This embodiment provides a positive electrode sheet, which includes a foil material, a first active structure, a second active structure, a third active structure and a fourth active structure. The foil material is aluminum foil, and the oil absorption value B of the conductive agent is 300ml / 100g;

[0095] The particle size D of the first main material in the first active structure 50 D1 = 0.4 μm, the mass ratio of the first main material: the first binder: the first conductive agent is 100:2.2:1, and the specific surface area A1 of the first conductive agent is 90 m 2 / g;

[0096] The particle size D of the second main material in the second active structure 50 D2 = 0.9 μm, the mass ratio of the second main material: the second binder: the second conductive agent is 100:2.2:1, and the specific surface area A2 of the second conductive agent is 90 m 2 / g;

[0097] The particle size D of the third main material in the third active structure 50D3 = 0.9 μm, the mass ratio of the third main material: the third binder: the third conductive agent is 100: 2.2: 0.4; the specific surface area A3 of the third conductive agent is 30 m 2 / g;

[0098] Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.4 μm, the mass ratio of the fourth main material: the fourth binder: the fourth conductive agent is 100: 2.2: 0.4, and the specific surface area A4 of the fourth conductive agent is 30 m 2 / g.

[0099] 1) Ingredients: a first slurry for forming a first active structure, a second slurry for forming a second active structure, a third slurry for forming a third active structure, and a fourth slurry for forming a fourth active structure are respectively prepared; each slurry contains active materials, conductive agents, binders and solvents, wherein the active materials are all iron phosphate particles, the conductive agent is carbon black, and the binder is selected from polytetrafluoroethylene. The particle size of the active material in each slurry, the oil absorption value and specific surface area of ​​the conductive agent, and the proportion of the active material, conductive agent and binder are respectively consistent with the corresponding active structure on the electrode.

[0100] 2) coating and layering: using a first coating die head to coat the first slurry and the third slurry on the surface of the aluminum foil to form a first active structure and a third active structure, using a second coating die head to coat the second slurry and the fourth slurry to form a second active structure and a fourth active structure, and baking and rolling to prepare a positive electrode sheet.

[0101] Example 2

[0102] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0103] The particle size D of the second main material in the second active structure 50 D2 = 1.1 μm, the particle size D of the third main material in the third active structure 50 D3=1.1μm.

[0104] Example 3

[0105] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0106] The particle size D of the second main material in the second active structure 50 D2 = 1.3 μm, the particle size D of the third main material in the third active structure 50 D3=1.3μm.

[0107] Example 4

[0108] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0109] The particle size D of the second main material in the second active structure 50 D2 = 1.1 μm; the particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; the specific surface area A4 of the fourth conductive agent is 50m 2 / g.

[0110] Example 5

[0111] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0112] The particle size D of the second main material in the second active structure 50 D2 = 1.1 μm; the particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 60 m 2 / g; the specific surface area A4 of the fourth conductive agent is 60m 2 / g.

[0113] Example 6

[0114] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0115] The mass ratio of the first main material: the first adhesive: the first conductive agent is 100:2.2:0.7; the mass ratio of the second main material: the second adhesive: the second conductive agent is 100:2.2:0.7; the mass ratio of the third main material: the third adhesive: the third conductive agent is 100:2.2:0.7; the mass ratio of the fourth main material: the fourth adhesive: the fourth conductive agent is 100:2.2:0.7.

[0116] Example 7

[0117] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0118] The particle size D of the first main material in the first active structure 50 D1 = 0.3 μm; the particle size D of the second main material in the second active structure 50 D2 = 1.1 μm; the particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.3 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0119] Example 8

[0120] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0121] The particle size D of the first main material in the first active structure 50 D1 = 0.6 μm; the particle size D of the second main material in the second active structure 50 D2 = 1.1 μm; the particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.6 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0122] Example 9

[0123] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0124] The particle size D of the first main material in the first active structure 50 D1 = 0.6 μm, and the specific surface area A1 of the first conductive agent is 80 m 2 / g; Particle size D of the second main material in the second active structure 50 D2 = 1.1 μm, and the specific surface area A2 of the second conductive agent is 80 m 2 / g; Particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.6 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0125] Example 10

[0126] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0127] The particle size D of the first main material in the first active structure 50 D1 = 0.6 μm, and the specific surface area A1 of the first conductive agent is 110 m 2 / g; Particle size D of the second main material in the second active structure 50 D2 = 1.1 μm, and the specific surface area A2 of the second conductive agent is 110 m 2 / g; Particle size D of the third main material in the third active structure 50D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.6 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0128] Embodiment 11

[0129] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0130] The oil absorption value B of the conductive agent is 260 ml / 100 g. The particle size D of the first main material in the first active structure is 50 D1 = 0.6 μm, and the specific surface area A1 of the first conductive agent is 110 m 2 / g; Particle size D of the second main material in the second active structure 50 D2 = 1.1 μm, and the specific surface area A2 of the second conductive agent is 110 m 2 / g; Particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.6 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0131] Example 12

[0132] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0133] The oil absorption value B of the conductive agent is 350 ml / 100 g. The particle size D of the first main material in the first active structure is 50 D1 = 0.6 μm, and the specific surface area A1 of the first conductive agent is 110 m 2 / g; Particle size D of the second main material in the second active structure 50 D2 = 1.1 μm, and the specific surface area A2 of the second conductive agent is 110 m 2 / g; Particle size D of the third main material in the third active structure 50 D3 = 1.1 μm, and the specific surface area A3 of the third conductive agent is 50 m 2 / g; Particle size D of the fourth main material in the fourth active structure 50 D4 = 0.6 μm, and the specific surface area A4 of the fourth conductive agent is 50 m 2 / g.

[0134] Example 13

[0135] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0136] The first active structure is the same as the third active structure, and the particle size of the first main material and the particle size of the third main material are D 50 Both are D1=0.4μm.

[0137] The second active structure and the fourth active structure are different. The particle size D of the second main material 50 D2 = 0.9 μm; the particle size of the fourth main material D 50 D4=0.4μm.

[0138] Comparative Example 1

[0139] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0140] The first active structure is the same as the second active structure, and the particle size D of the first main material is 50 D1 = 0.4 μm;

[0141] The third active structure is the same as the fourth active structure, and the particle size D of the third main material is 50 D3=1.1μm.

[0142] Comparative Example 2

[0143] This embodiment provides a positive electrode sheet, which is basically the same as that of Embodiment 1, except that:

[0144] The first active structure, the second active structure, the third active structure and the fourth active structure are the same, and the particle size D of the main material 50 The surface area of ​​the conductive agent is 0.9 μm, the mass ratio of the main material: binder: conductive agent is 100:2.2:0.4, and the specific surface area A1 of the conductive agent is 30 m 2 / g.

[0145] In Examples 1-13 and Comparative Examples 1-2, the conductive agents are all carbon black, the binders are all polytetrafluoroethylene, the main material is lithium iron phosphate, and the first active layer and the second active layer are arranged on aluminum foil. The positive electrode sheet, the corresponding negative electrode sheet, and the separator are assembled into a battery.

[0146] The relevant information of the active structures provided by the above Examples 1-13 and Comparative Examples 1-2 is shown in Table 1 below.

[0147] Table 1

[0148]

[0149] The electrochemical performance of each battery assembled in the above examples and comparative examples was subjected to a 50% SOC DC internal resistance test and a liquid phase diffusion impedance test, and the test conditions were as follows:

[0150] 50% SOC DC internal resistance test: At room temperature 25±5℃, the battery is discharged to 2.0V at 1 / 3C constant current, charged to 50% SOC at 1 / 3C constant current, and left for 30min; discharged at 1.5C constant current for 30s, and the 50% SOC DC internal resistance is detected.

[0151] Liquid phase diffusion impedance test: Assemble the above positive electrode sheets into a core; place the core in an outer packaging shell, bake and inject electrolyte, and obtain a liquid phase diffusion impedance battery after packaging, infiltration and other processes. Use an electrochemical workstation to perform liquid phase diffusion impedance test in the frequency range of 300000Hz-0.05Hz. The electrode liquid and negative electrode sheet are conventional materials in this field.

[0152] The test results are shown in Table 2 below.

[0153] Table 2

[0154] 50%SOC DCIR(Ω) Liquid phase diffusion impedance (Ω) 2C / 0.2C discharge ratio Example 1 0.787 0.464 0.87 Example 2 0.747 0.391 0.91 Example 3 0.802 0.389 0.88 Example 4 0.671 0.341 0.94 Example 5 0.877 0.402 0.89 Example 6 0.912 0.478 0.85 Example 7 0.786 0.488 0.89 Example 8 0.815 0.475 0.84 Example 9 0.823 0.493 0.82 Example 10 0.888 0.509 0.8 Embodiment 11 0.851 0.513 0.73 Example 12 0.874 0.479 0.75 Embodiment 13 1.017 0.527 0.70 Comparative Example 1 1.266 0.563 0.66 Comparative Example 2 1.493 0.603 0.63

[0155] Comparing Examples 4-5 in Table 1 and Table 2, when the specific surface area of ​​the conductive agent of the third active structure and the fourth active structure increases and other conditions are the same, the impedance of the battery increases and the rate discharge retention ratio decreases.

[0156] Comparing Example 1 and Example 6 in Table 1 and Table 2, the mass of the first conductive agent and the second conductive agent of Example 6 is the same as the mass of the third conductive agent and the fourth conductive agent. The impedance of the battery of Example 6 increases, and the rate discharge retention ratio increases.

[0157] Comparing Examples 7-8 in Table 1 and Table 2, when the particle sizes of the first main material and the fourth main material increase and other conditions are the same, the rate discharge retention ratio decreases.

[0158] Comparing Examples 8-10 in Table 1 and Table 2, when the specific surface area of ​​the first conductive agent and the second conductive agent increases and other conditions are the same, the impedance of the battery first decreases and then increases, and the rate discharge retention first increases and then decreases.

[0159] Comparing Examples 10-12 in Table 1 and Table 2, when the oil absorption value of the conductive agent increases and other conditions are the same, the liquid phase diffusion impedance of the battery decreases.

[0160] Comparing Example 1 and Example 13 in Table 1 and Table 2, the particle sizes of the first main material and the third main material of Example 13 are the same, and the particle sizes of the first main material and the third main material of Example 1 are different. The rate discharge retention rate of the battery of Example 13 is lower than the rate discharge retention rate of the battery of Example 1, and the impedance of the battery of Example 13 is greater than the impedance of the battery of Example 1.

[0161] When comparing Examples 1-13 and Comparative Examples 1-2 in Tables 1 and 2, the impedance of the batteries of Examples 1-13 is smaller than the impedance of the batteries of Comparative Examples 1-3, and the rate discharge retention factors of the batteries of Examples 1-13 are greater than the rate discharge retention factors of the batteries of Comparative Examples 1-2.

[0162] In summary, a first active layer and a second active layer are stacked on the foil, and the particle size D of the main material of the first active structure in the first active layer is 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure in the second active layer 50 Smaller than the particle size D of the main material of the third active structure 50 That is, the active material layer is arranged into areas with different particle sizes, so that straight through holes are directly formed at the interface of large and small particles during the rolling process, thereby realizing the regulation of the pore size in the longitudinal vertical direction, reducing the tortuosity of the thick electrode, increasing the infiltration of the electrolyte and the longitudinal diffusion channel of ions, and optimizing the battery kinetic performance.

[0163] In the description of the embodiments of the present invention, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0164] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.

Claims

1. A pole piece, characterized in that: include: Foil; A first active layer, stacked on the foil, the first active layer comprising a first active structure and a second active structure connected to each other; A second active layer is stacked on the first active layer, the second active layer includes a third active structure and a fourth active structure connected to each other, the third active structure is stacked on the first active structure, and the fourth active structure is stacked on the second active structure; The particle size D of the main material of the first active structure 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

2. The pole piece according to claim 1, characterized in that: The particle size D of the main material of the first active structure 50 Smaller than the particle size D of the main material of the second active structure 50 ; and the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

3. The pole piece according to claim 2, characterized in that: The first active structure comprises a first main material, and the particle size D of the first main material is 50 D1 satisfies: 0.3 μm ≤ D1 ≤ 0.6 μm, the second active structure has a second main material, and the particle size D 50 is D2, satisfying: 0.9 μm ≤ D2 ≤ 1.3 μm; the third active structure has a third main material, and the particle size D of the third main material is 50 is D3, satisfying: 0.9 μm ≤ D3 ≤ 1.3 μm, the fourth active structure has a fourth main material, the particle size D of the fourth main material 50 It is D4, satisfying: 0.3μm≤D4≤0.6μm.

4. The pole piece according to claim 3, characterized in that: The first active structure has a first conductive agent, and the specific surface area of ​​the first conductive agent is A1, which satisfies: 80m 2 / g≤A1≤110m 2 / g, the second active structure has a second conductive agent, the specific surface area of ​​the second conductive agent is A2, and satisfies: 80m 2 / g≤A2≤110m 2 / g; the third active structure has a third conductive agent, the specific surface area of ​​the third conductive agent is A3, satisfying: 30m 2 / g≤A3≤60m 2 / g, the fourth active structure has a fourth conductive agent, the specific surface area of ​​the fourth conductive agent is A4, and satisfies: 30m 2 / g≤A4≤60m 2 / g.

5. The pole piece according to claim 4, characterized in that: The first active structure also has a first binder, and the mass ratio of the first main material, the first binder and the first conductive agent is 100: (2.0-2.5): (0.6-1.2); the second active structure also has a second binder, and the mass ratio of the second main material, the second binder and the second conductive agent is 100: (2.0-2.5): (0.6-1.2); the third active structure also has a third binder, and the mass ratio of the third main material, the third binder and the third conductive agent is 100: (2.0-2.5): (0.2-0.6); the fourth active structure also has a fourth binder, and the mass ratio of the fourth main material, the fourth binder and the fourth conductive agent is 100: (2.0-2.5): (0.2-0.6).

6. The pole piece according to claim 4, characterized in that: The oil absorption values ​​of the first conductive agent, the second conductive agent, the third conductive agent and the fourth conductive agent are B, and satisfy: 240 ml / 100 g≤B≤320 ml / 100 g.

7. The pole piece according to claim 1, characterized in that: The first active layer includes a plurality of the first active structures and a plurality of the second active structures, and the plurality of the first active structures and the plurality of the second active structures are arranged alternately. The second active layer includes a plurality of the third active structures and a plurality of the fourth active structures, and the plurality of the third active structures and the plurality of the fourth active structures are arranged alternately.

8. A method for preparing a pole piece, characterized in that: The steps include: Provide foil; Laying a first active structure and a third active structure on the foil, and laminating a second active structure and a fourth active structure on the foil on the same side of the first active structure and the third active structure; The first active structure and the second active structure are connected to form a first active layer, the third active structure and the fourth active structure are connected to form a second active layer, and the particle size D of the main material of the first active structure is 50 Smaller than the particle size D of the main material of the second active structure 50 ; or the particle size D of the main material of the fourth active structure 50 Smaller than the particle size D of the main material of the third active structure 50 .

9. The method for preparing a pole piece according to claim 8, characterized in that: The method comprises: stacking a first active structure and a third active structure on the foil material, and stacking a second active structure and a fourth active structure on the foil material on the same side of the first active structure and the third active structure, comprising: Providing a first coating die and a second coating die; Providing a slurry, wherein the slurry includes a first slurry, a second slurry, a third slurry, and a fourth slurry; The first coating die coats the first slurry and the third slurry on the foil to form the first active structure and the third active structure, and the second coating die coats the second slurry and the fourth slurry on the foil to form the second active structure and the fourth active structure.

10. A battery cell, characterized in that: It comprises a diaphragm and a pole piece as described in any one of claims 1 to 7, wherein the diaphragm and the pole piece are stacked.

11. A battery, characterized in that: It comprises a shell and the battery core as claimed in claim 10, wherein the battery core is accommodated in the shell.

12. An electrical device, characterized in that: The invention comprises an electric device and the battery as claimed in claim 11, wherein the battery supplies power to the electric device.

Citation Information

Patent Citations

  • Negative pole piece, preparation method thereof and secondary battery

    CN114927639A

  • Lithium-sulfur battery positive plate, preparation method thereof and lithium-sulfur battery

    CN115692602A

  • Electrode plate, battery, battery pack and electric equipment

    CN116314591A

  • Negative electrode material layer, negative electrode plate, preparation method of negative electrode plate, secondary battery, battery pack and electric equipment

    CN116435503A

  • Electrode plate, secondary battery and terminal device

    WO2023185743A1